Leucine-rich repeat-containing 56 promotes breast cancer progression via modulation of the RhoA/ROCKs signaling axis - Xiqian Zhou; Jiaxin Wang; Meiling Lu; Lin Fang; Junyong Zhao; Dengfeng Li (Molecular Biomedicine)
Abstract Breast cancer is one of the most common malignancies with a poor five-year survival rate with metastatic disease among women. It has well been documented that leucine-rich repeat-containing (LRRC) family of proteins are remarkably and aberrantly dysregulated across diverse cancer types. Notably, leucine-rich repeat-containing 56 (LRRC56) was found upregulated in metastatic breast cancer, and plays a crucial role for the movement of cilia via intraflagellar transport 88 (IFT88). However, the role for LRRC56 in breast cancer progression and regulation of IFT88 and associated pathways in metastatic progression of breast cancer has not been defined. Via in vitro functional assessments, we found that LRRC56 pivotally influences the proliferative, migratory and invasive capabilities of cancer cells. Further, via in-vivo assessments, we demonstrated that downregulation of LRRC56 effectively inhibits the growth of breast cancer xenograft tumors and their metastasis to the lungs. Mechanistically, we found that LRRC56 interacts with IFT88 to regulate yes-associated protein 1 (YAP1) expression via modulating the Ras homolog family member A (RhoA)/ Rho-associated protein kinases (ROCKs) signaling pathway. LRRC56 also regulates the expression of integrins and several other key molecules including MMP2, MMP9, FAK, as well as markers of epithelial-mesenchymal transition such as E-cadherin and N-cadherin. In summary, our results demonstrate that overexpression of LRRC56 promotes breast cancer progression via upregulating IFT88/YAP1-RhoA/ROCKs pathway, reprogramming extracellular matrix, and enhancing epithelial-mesenchymal transition. These findings highlight a critical role of LRRC56 in promoting breast cancer progression, suggesting that targeting of LRRC56 may offer a promising strategy for treating metastatic breast cancer.